An ancient theatre dynasty: the elder Carcinus, the young Xenocles and the sons of Carcinus in Aristophanes - Stewart, Edmund (Akademie Verlag, 2016)
The elder Carcinus and his sons are mentioned, or appear on stage, as tragic performers in three plays by Aristophanes (Wasps, Clouds and Peace). They provide a unique insight into how the performance of tragedy could be (and frequently was) a family business. This study attempts to establish what can be known about this theatrical family from the evidence of comedy and how it functioned as an acting troupe. Moreover, in examining how the family troupe changed over time, we begin to learn more about the process by which one of Carcinus’ sons, Xenocles, was trained as a tragic poet. Though little is known about Carcinus, Xenocles was a relatively successful tragedian, who was active in the final two decades of the fifth century B.C. Both ancient and modern scholars have assumed that Xenocles was a poet by 422, when he is thought to have appeared as a character in the Wasps. I argue that Xenocles did not in fact make his debut as an independent poet until after 420. Before this date Aristophanes recognises Carcinus as the poet of the family company, which suggests that the young Xenocles was still serving his apprenticeship with his father at this time.